PENGARUH LITERASI KEUANGAN SYARIAH DAN PERENCANAAN KEUANGAN SYARIAH TERHADAP MINAT MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG BERINVESTASI PADA PASAR MODAL SYARIAH - Adibah, Ayuk Wahdanfiari (Institut Agama Islam Ngawi, 2024)
Investment activities generate income, both in the present and in the future. Therefore, an investor must understand and carefully plan their investments before making decisions. This study aims to investigate the influence of Islamic financial literacy and Islamic financial planning on students' interest in investing in the Islamic stock exchange, both partially and simultaneously. The approach used is quantitative, with data collected through questionnaires distributed to all students of the FEBI at UIN Sayyid Ali Rahmatullah Tulungagung, class of 2022. The sampling technique applied is purposive accidental sampling, and data analysis was conducted using the SPSS 21 program. The data analysis method employed in this research is multiple linear regression analysis, with data instrument tests including validity and reliability tests, as well as classical assumption tests such as normality, autocorrelation, multicollinearity, and heteroscedasticity tests. Hypothesis testing and the coefficient of determination test were also performed. The results of the study indicate that 1) Islamic financial literacy significantly influences students' interest in investing in the sharia stock exchange, 2 Islamic financial planning also has a significant impact on students' interest in investing in the stock exchange, and 3) Islamic financial literacy and Islamic financial planning together have a significant effect on students' interest in investing in the sharia stock exchange.Keywords: sharia financial literacy, sharia financial planning, sharia investing